A Study of Development of Smart Cities Using Internet of Things - Hee-woong, Jeong (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Smart cities as well as the unique services they provide by using current technology and innovative solutions are taking on a major role in the development of the information society. The Internet of Things is the most important factor in enabling and driving smart cities (IoT). In this article, the researcher has investigated potential Internet of Things-based smart city services by conducting a systematic literature analysis and reporting their findings. The researcher has developed the protocol for the review in order to specify the research topic or issues, the research methodology, the selection process, the criteria for evaluating the reliability of the research, as well as the method for information gathering. The following is the main study issue that the researcher has defined: In the context of the advancement of smart city services, what kinds of applications have been identified for the Internet of Things? The studies were organised into groups according to the smart city services they either described or suggested. The researcher has identified the following categories: transportation and traffic, environmental monitoring, accessibility and medical care, management of trash and resources, public lighting, management of energy resources, municipal infrastructure, and many other.